2021
DOI: 10.1001/jamanetworkopen.2021.17416
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vision Impairment With Cognitive Decline Across Multiple Domains in Older Adults

Abstract: IMPORTANCE Associations between visual and global cognitive impairments have been previously documented, but there is limited research examining these associations between multiple measures of vision across cognitive domains. OBJECTIVE To examine the association between vision and cognitive across multiple cognitive domains using multiple measures of vision. DESIGN, SETTING, AND PARTICIPANTS This longitudinal cohort study used data from the Baltimore Longitudinal Study of Aging for 2003 to 2019. Participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 49 publications
(91 reference statements)
0
28
0
Order By: Relevance
“…Recent systematic reviews and meta-analyses found that VI was significantly associated with cognitive impairment in cross-sectional and longitudinal studies [ 16 , 17 ]. In a longitudinal cohort study, it was found that worse visual acuity at baseline was associated with greater declines in language and memory domains of cognitive function [ 18 ]. Although the causality between the VI and cognitive impairment remains to be investigated, the value of screening elders for visual impairment and optimizing their vision could potentially contribute to the prevention of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses found that VI was significantly associated with cognitive impairment in cross-sectional and longitudinal studies [ 16 , 17 ]. In a longitudinal cohort study, it was found that worse visual acuity at baseline was associated with greater declines in language and memory domains of cognitive function [ 18 ]. Although the causality between the VI and cognitive impairment remains to be investigated, the value of screening elders for visual impairment and optimizing their vision could potentially contribute to the prevention of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to 4 longitudinal studies and one meta-analysis that have found a relationship between VI and cognitive function [12][13][14]53,54 and 1 study that found a relationship between visual acuity, used as a continuous variable, and cognitive decline. 55 Furthermore, several studies have found a relationship between VI and dementia or cognitive impairment [56][57][58][59][60] although not all. 61 Of note, some of these studies used cognitive tests that relied on vision without removing the visual items (MMSE, 3 MS).…”
Section: Discussionmentioning
confidence: 99%
“…Just to provide an example, it was demonstrated that sensory functions impairments have a direct role in cognitive aging, since good sensory functions, with particular regard to visual task, were found strongly predictive of the cognitive performance (Glass, 2007). Interestingly, each visual function has a different impact on cognitive impairment, with contrast sensitivity seeming to have the strongest relationship with cognitive tests scores (Varadaraj et al, 2021). It is worth of notice that glaucomatous patients are characterized by significantly higher impairment of contrast sensitivity, with respect to normal aging (McKendrick et al, 2007).…”
Section: Cognitive Impairment In Glaucomamentioning
confidence: 99%